ChemInform Abstract: Valuable Insight into the Synthesis and Biological Activities of Fused Heterocyclic Nucleus Using Microwave. Issue 50 (16th December 2014) - Chawla, Anshul; Kaur, Harmanjit
Abstract Review: 146 refs.